Pengembangan Media Pembelajaran Genially Pada Materi Negaraku Kaya Sumber Daya Alam Kelas V SD - Gusti Nawang Sari; Putri Juwita; Tiflatul Husna; Beta Rapita Silalahi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to develop Genially-based learning media on the material "My Country is Rich in Natural Resources". The method used is Research and Development (R&D) with the ADDIE development model consisting of the stages of analysis, design, development, implementation and evaluation. The research subjects involved media experts and material experts as validators of products and student responses. And the object of research is the development of Genially learning media. Data collection instruments in the form of observation, interviews, and validation questionnaires were used to assess the feasibility of media and learning materials. This study was conducted on June 3-June 11, 2025. The validation results showed that the Genially learning media obtained a feasibility percentage of 70.66% from media experts (valid category) and 84% from material experts (very valid category), so it was declared suitable for use in the learning process. Product trial data was also carried out with a student response questionnaire filled out by 16 students, with a percentage of 92.74% indicating that this media is suitable for use. This media is expected to help students' understanding of natural resources material, as well as provide innovative alternatives for teachers in delivering technology-based learning.